Sistem Informasi Geografis Berbasis Web Pemetaan Lokasi Sanggar Kesenian di Provinsi Bali - Putu Wahyu Saputra; I kadek Andy Asmarajaya; Kadek Oky Sanjaya (RESI : Jurnal Riset Sistem Informasi, 2026)
In 2022, the Bali Provincial Culture Office implemented a standardization and certification program for art institutions in Bali Province. This program aims to improve the quality of art studios through quality control, better management of studio organizations, and efficiency in the implementation of art activities in the community. To support these goals, a data-driven information center about art studios in Bali is needed that utilizes technological advances. This study aims to develop a web-based geographic information system that maps the location of art studios in Bali Province using data from the results of standardization and certification of art institutions. The system was developed using the PHP programming language, with digital maps displayed through the LeafletJS library and utilizing base maps from OpenStreetMap. Studio locations are marked using markers based on latitude and longitude coordinates. The system development utilizes the Agile methodology, while system testing is conducted using the Black Box method that focuses on the functional aspects of the software.